COVID-19 vaccine hesitancy among youth. Issue 12 (2nd December 2021) - Willis, Don E.; Presley, Jessica; Williams, Mark; Zaller, Nickolas; McElfish, Pearl A.
ABSTRACT: The purpose of this evaluation is to describe COVID-19 vaccine hesitancy among a sample of youth aged 12–15 and inform efforts to increase vaccination uptake among youth populations. We used data collected in May 2021 through a health education program for 9 th graders (N = 345). We used Spearman correlations and chi-square tests to assess the statistical significance of bivariate relationships. Less than half of students (42%) reported they are not hesitant at all about getting a COVID-19 vaccine. The remainder reported they were "a little hesitant" (22%), "somewhat hesitant" (21%), or "very hesitant" (15%). There were no statistically significant differences across age, gender, race/ethnicity, parental education, self-reported grades, or hours playing video games during school days. There was a statistically significant relationship between COVID-19 vaccine hesitancy and hours of TV watched during school days. The prevalence of COVID-19 vaccine hesitancy in this sample is high, but more research is needed to estimate its prevalence for youth at the state or national level. Correlates of COVID-19 vaccine hesitancy among adult populations may not match those found in youth populations. Research which recognizes youth as agentic rather than passive participants in decision-making opens opportunities for developing age-appropriate health communication and interventions for vaccination.